PENTINGNYA PEMENUHAN GIZI PADA BAYI DAN BALITA PADA MASA PANDEMI COVID-19 - Ririn Handayani; Yuningsih yuningsih; Laila Karimatu Zalika (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2021)
The high rate of child mortality due to Covid-19 can be triggered by several factors, namely low examination rates, many children have congenital diseases and suffer from poor nutrition, and delayed treatment. One of the steps that need to be taken to make this condition worse is to maintain immunity in children, among others, by eating foods with balanced nutrition, maintaining health protocols and maintaining health. The purpose of this activity is as a preventive effort in order to reduce the mortality rate of infants and toddlers with Covid-19 through increasing immunity through adequate balanced nutrition. This Community Service activity was carried out at Posyandu Aster 11 and 15 Tegal Besar Village in the Kaliwates Health Center. Target in this activity is all mothers who have babies and toddlers. The results of Community Service activities showed that the nutritional status of infants and toddlers based on BB/U obtained 4 toddlers (4percent) in the category of poor nutritional status, 16 toddlers (18percent) with the category of poor nutritional status, 70 toddlers (77percent) in the good nutrition category, 1 toddler (1percent) with more nutritional status category. From the data above, it is hoped that this Community Service activity can increase the knowledge of mothers about the importance of fulfilling nutrition for infants and toddlers so that mothers are able to improve the nutritional status of children with the hope that body immunity will increase and be able to reduce morbidity and mortality rates in infants and toddlers, especially due to the Covid-19 virus.